Three-dimensional CAD-based mesh Generator for the Dey-Mittra conformal FDTD algorithm - Waldschmidt, G.; Taflove, A. (IEEE transactions on antennas and propagation, 2004)
It is well-known that the finite-difference time-domain (FDTD) method is subject to significant errors due to the staircasing of surfaces that are not precisely aligned with major grid planes. Dey and Mittra introduced a locally conformal method (D-FDTD) that has shown substantial gains in the accuracy of modeling arbitrary surfaces in the FDTD grid. A mesh generator for this purpose was reported by Yu and Mittra. In this paper, we present the formulation and validation of an alternative CAD-based mesh generator for D-FDTD that has improved capabilities for arbitrary three-dimensional (3-D) perfect electric conductor (PEC) geometries. This mesh generator is capable of importing AutoCad and ProE files of 3-D PEC scatterers and resonators. It can reduce the required FDTD grid resolution by up to 4:1 in each Cartesian direction in 3-D relative to conventional staircased FDTD models when modeling cavity resonances of complex PEC structures such as twisted waveguides.